Severity of Work Disability and Work - Oguzoglu, U (My University, 2007)
At any given time, individuals may be subject to health shocks whose impact on work capacity can vary in magnitude. Therefore the variation in severity levels can explain changes in labour force decisions that can not be picked up by the general disability status alone. This paper analyses the effect of severity of disability on labour force participation by using two measures of severity: the self-reported work limitation scales and the SF-36 physical component summary scores. Using five waves of the Household, Income and Labour Dynamics in Australia Survey, several static and dynamic panel data models are estimated to account for state dependence and unobserved heterogeneity in participation. The results suggest that differences in severity levels explain a significant portion of the variance in the participation rates among disabled individuals. It is also found that severe work limitations have a more immediate impact on individuals’ labour force outcomes. Moreover, the disabilities are shown to have longer lasting adverse effects on female participation.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Employment; Health; Health -- Disability; Health and wellbeing; Labour market; Health; Employment and unemployment